Long-term prednisone versus hydrocortisone treatment in children with classic Congenital Adrenal Hyperplasia (CAH) and a brief review of the literature - Ahmed , Shaymaa Elsayed Abdel Meguid; Soliman , Ashraf T; Ramadan , Magdy A; Elawwa , Ahmed; Abugabal , Ahmed Mohamed Said; Emam, Mohamed Hassan Ahmed; De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2019)
Background: Debate still exist about the safety of long-term use of prednisone (PD) versus hydrocortisone (HC) for treating children with congenital adrenal hyperplasia -21OH D (CAH). Despite recent developments in congenital adrenal hyperplasia -21OH D (CAH), several issues related to patient growth and final height remain unsolved. Debate still exist about the safety of long-term use of PD versus HC for treating children with CAH. The mechanism by which glucocorticoid therapy interferes with growth is complex and multifactorial. Relatively slight supra-physiologic levels may be enough to blunt growth velocity. An increased risk of developing obesity is another possible consequence of hyper-cortisolism in children with CAH. Objectives of the study: To evaluate the anthropometric and biochemical effects of long-term PD versus HC treatment in children with CAH-21OHD. A brief review of the literature is also reported. Patients and Methods: This retrospective study evaluated linear growth and biochemical data of thirty children with classic CAH (19 females and 11 males), who were on PD (n=22) or HC (n=8) treatment, since their first diagnosis. Clinical data included age, gender, duration of therapy, dose of HC and or equivalent dose of HC in the PD group, blood pressure, height (Ht) and weight. Ht-SDS and BMI were also calculated. Biochemical data included measurement of 17- OH progesterone, cholesterol, triglycerides (TG), HDL, LDL, fasting glucose, and insulin concentrations. HOMA-IR was calculated. Carotid intima-media thickness (CIMT) was measured using high-resolution B-mode ultrasonography. Thirty normal age matched children were used as controls for the anthropometric and CIMT data. Results: The age of children and duration of treatment did not differ among the two treatment groups. After a mean of 6 years of treatment, the Ht-SDS and BMI did not differ between the three groups of children. The equivalent hydrocortisone dose of children on prednisone was significantly higher than the dose for the hydrocortisone group. Both systolic and diastolic blood pressures (BP) of children on PD was slightly higher compared to those on hydrocortisone group. However, the BP of the 2 treatment groups was not different compared to control children. Fasting blood glucose, homeostatic model assessment insulin resistance (HOMA-IR), plasma TG, HDL, and cholesterol did not differ among the two treatment groups. LDL levels were significantly higher in the PD group versus the HC group. The mean CIMT did not differ among the two treatment groups but was significantly higher in the treated groups versus controls. There was a significant linear correlation between BMI-SDS and CIMT (r=0.37, p=0.047). Conclusions: Children with CAH-21OHD who were kept on PD therapy for 6.4±2.7 years, since the beginning of diagnosis, have maintained normal linear growth. No difference in BMI, HOMA-IR, or CIMT was detected among the two treated groups. The efficiency, safety and convenience of a single daily dose of PD could be a good and relatively safe alternative to HC for the continuing medical treatment of patients with CAH-21OHD. However, more prospective studies across childhood and adolescence are necessary to draw definitive conclusions.